IMPROVING STUDENTS' VOCABULARY MASTERY BY USING THE RUMAH BELAJAR APPLICATION AT ONE OF JUNIOR HIGH SCHOOLS - Atia, Nurul; Rachmawati, Rachmawati; Yanto, Yanto (Langue (Journal of Language and Education), 2022)
ABSTRACT Vocabulary is an important factor in learning a language. People cannot hear, speak, read, and write without knowing vocabulary. Likewise in learning a foreign language such as English, vocabulary plays a very important role. However, not all junior high school students learn vocabulary in English easily. This is caused by several factors including learning media that are less attractive so that children get bored quickly, teaching methods or techniques of teachers who are not creative and monotonous, and teaching and learning activities that are more dominated by teachers without involving or involving students to participate. Rumah Belajar application is one of application used in learning and found a new understanding of the new media used by the teacher in media online learning. In this research, the researcher used Classroom Action Research as the design method. The data was collected from the seventh grade which has been learned using Rumah Belajar. The sample was 24 students selected by purposive sampling. The research found that the majority of students had a positive perception of Rumah Belajar in learning based on the results of their interviews. They improved their vocabulary learning through the Rumah Belajar application in learning and found a new understanding of the new media used by the teacher in media online learning. On the other hand, some students gave the perception that online learning has obstacles affected by a poor network, the quality of the student's mobile phone, and the capacity of the online learning application. Keywords: Vocabulary, Rumah Belajar, Application.